2022
DOI: 10.3892/mmr.2022.12763
|View full text |Cite
|
Sign up to set email alerts
|

CTRP12 alleviates cardiomyocyte ischemia‑reperfusion injury via regulation of KLF15

Abstract: Myocardial ischemia-reperfusion (I/R) serves a crucial role in myocardial infarction. C1q/TNF-related protein 12 (CTRP12) is a secretory protein involved in metabolism. It has been reported that CTRP12 participates in the regulation of numerous cardiovascular diseases. However, its role in myocardial I/R injury remains unclear. In the present study, the left anterior descending coronary artery in mice was ligated to establish a mouse I/R model. A myocardial hypoxia-reoxygenation (H/R) cell model was also estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Similar to other CTRPs that have by now been analyzed for their impact on the heart, CTRP9 revealed to be largely protective in different types of disease models including myocardial infarction, I/R injury, LPS-induced cardiac dysfunction, pulmonary arterial banding and atrial fibrillation [31,32,49,[51][52][53][54][55] (Table 2). Cardiac protection after myocardial infarction and/or experimental I/R injury was also reported for CTRP1, CTRP2, CTRP3, CTRP12 and CTRP15 [56][57][58][59][60][61]. Strikingly, however, CTRP9 was found to aggravate pressure overload-induced heart failure suggesting that under these special conditions CTRP9 either exceeds an optimal concentration, or that CTRP9 might be processed differently resulting in altered receptor or co-receptor usage [45].…”
Section: Ctrpmentioning
confidence: 69%
“…Similar to other CTRPs that have by now been analyzed for their impact on the heart, CTRP9 revealed to be largely protective in different types of disease models including myocardial infarction, I/R injury, LPS-induced cardiac dysfunction, pulmonary arterial banding and atrial fibrillation [31,32,49,[51][52][53][54][55] (Table 2). Cardiac protection after myocardial infarction and/or experimental I/R injury was also reported for CTRP1, CTRP2, CTRP3, CTRP12 and CTRP15 [56][57][58][59][60][61]. Strikingly, however, CTRP9 was found to aggravate pressure overload-induced heart failure suggesting that under these special conditions CTRP9 either exceeds an optimal concentration, or that CTRP9 might be processed differently resulting in altered receptor or co-receptor usage [45].…”
Section: Ctrpmentioning
confidence: 69%
“…27 It was reported that TNF-α was involved with the development of hypertension and coronary heart disease. 28,29 Elabela was detected in stem cells, kidneys, prostate, vascular endothelium and plasma. 30 Differences in the plasma levels of apelin and elabela were reported in patients with gestational diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, plasma elabela levels decreased in CVDs such as atrial fibrillation with hypertension 26 and coronary heart disease 27 . It was reported that TNF‐α was involved with the development of hypertension and coronary heart disease 28,29 . Elabela was detected in stem cells, kidneys, prostate, vascular endothelium and plasma 30 .…”
Section: Discussionmentioning
confidence: 99%